Cardiovascular Anthropometry: What Is Best Suited for Large-Scale Population Screening in Sub-Saharan Africa? - Agbo, Hadiza A.; Zoakah, Ayuba I.; Isichei, Christian O.; Sagay, Atiene S.; Achenbach, Chad J.; Okeahialam, Basil N. (Frontiers in Cardiovascular Medicine, 2020)
Background: Body Mass Index (BMI) measures overweight/obesity. It however especially in sub-Saharan Africa (SSA) misclassifies cardiometabolic risk. Central obesity measures are superior. We therefore sought to compare BMI, Waist to Hip Ratio (WHR) and Abdominal Height (AH) in predicting cardiovascular disease risk in sub-Saharan Africa. Methods: Subjects had blood pressures, BMI and WHR determined. Blood pressure was taken, weight and height measured to generate BMI; and AH measured with a new locally fabricated abdominometer. The ability of the anthropometric indices in identifying abnormal individuals, needing intervention was assessed with sensitivity, specificity and area under the receiver operator characteristic curve. Results: Adults totalling 1,508 (728 M/780 F) adults were studied. For BMI, 985 (65.3%) were normal while 375 (24.9%) consisting of 233 males and 142 females had normal WHR. Blood pressure was normal in 525 (34.8%) and 317 (21.0%) for systolic and diastolic blood pressures respectively. Using BMI as gold standard, sensitivity, specificity, positive and negative predictive values for WHR in males were 80.7%, 37.5%, 62.5% and 19.3% respectively. For females and in the same order it was 62.0%, 34.3%, 65.7% and 38.0%. For AH it was equal in both genders at 82.6%, 39.2%, 60.8% and 17.4%. By Receiver Operating Curves comparing AH, WHR and BMI against blood pressure detection, the area under the curve was 0.745, 0.604 and 0.554 for AH, BMI and WHR respectively. Conclusion: Abdominometer derived AH has a better sensitivity and greater area under the receiver operator curve compared with BMI and WHR in this sub-Sahara African population; implying superiority as a cardiovascular anthropometric index.